The Effects of Social Media Use on the Well-Being of Users. The Wonderland of HaikuJAM - Daniela Andrén (Örebro University School of Business, 2019)
Internet usage in general and social networking platforms (SNPs) in particular have dramatically changed the way we spend our time. A relevant question is how this change in time-use affected the well-being of people in general and younger people in particular. We answer this question by reporting, for the first time, detailed information about time-use in SNPs and the well-being of Jammers, the users of HaikuJAM (HJ), a mobile app that aims to boost emotional well-being using collaborative writing techniques. HaikuJAM is output-dependent. Our explorative analysis finds that Jammers who spent most of their SNP time in HJ have, on average, a slightly higher level of both life satisfaction and other domain satisfactions (especially satisfaction with family and friends) than the other Jammers. They also have a few sociodemographic characteristics that are statistically significant different from the other Jammers (i.e., they are slightly older and more of them work and are married). Predominant Jammers also have higher expectations about the importance of the use of HaikuJAM for their well-being and their personal development. Our results suggests that the app features attract a specific group of users who have a relatively high level of satisfaction with their life in general and with their family and friends, in particular. It is quite possible that creative individuals who might be introverts and/or are lonely are using HaikuJAM not only to write but also to connect with other individuals who like to write. Despite the fact that our analysis is largely exploratory, our results suggest a few possibilities to addresses the causality between users' time spent in a SNP and their well-being.
Keywords: A12; D60; I31; 330; well-being; life satisfaction; social networking platform; social media; communit; time-use; collaborative writing; poetry; haiku; HaikuJAM App; Jammers; predominant Jammers